The Institution of An Empirical Overview of India's Supreme Court (International Journal of Food and Nutritional Sciences, 2022)
A billion or more people fall within the jurisdiction of the Indian Supreme Court, making it "the most powerful court in the world" due to its extensive jurisdiction, broad knowledge of its own powers, and these factors. However, researchers and decision-makers have quite different perspectives on how the court operates: they know a lot about the more well-known, "high-profile" Very less is known about the less important but far more frequent and maybe equally important judgements. through address this imbalance, this chapter covers the Court's decisions from 2010 through 2015. We use the most extensive original dataset of Indian Supreme Court opinions that has yet to be created to provide a thorough, quantitative overview of the social identity of the litigants who approach the court, the types of matters they bring to the court, the levels of success that various groups of litigants have before the Court, and the opinion-writing patterns of the various Supreme Court judges. This investigation provides the crucial data for understanding the Court and its role in fostering societal change.